Factors Influencing Loyalty to Health Food Brands: An Analysis from the Value Perceived by the Peruvian Consumer - García-Salirrosas, Elizabeth Emperatriz (2022)
The COVID 19 pandemic brought significant changes in consumption habits, bringing about an era of more sustainable and healthier consumption. The objective of the present study is to measure brand loyalty to healthy foods in Peru, not only in a pandemic context, but also in a natural context based on the dimensions of the PERVAL value scale. Data were collected through an online survey and processed using partial least squares structural equation modeling (PLS-SEM). The results of the model among 396 consumers revealed that qualitative value and emotional value have the highest contribution to brand loyalty, followed by economic value and social value. These findings suggest that product quality should be taken as a priority and, although social value does not contribute much to health food brand loyalty, it is a trend sought after by consumers.